Pengaruh Fungsi Keluarga Terhadap penerimaan Diri Penderita Kanker Serviks Berdasarkan Tinjauan Literatur - Ananingati; Ricky Haryanto; Feny Tunjungsari; Moch. Ma’roef (ARTERI : Jurnal Ilmu Kesehatan, 2023)
Cervical cancer is one of the causes of death among women in various countries. The inability to face the reality that you have cervical cancer causes various psychological responses, including anxiety, sadness, denial of the diagnose of the disease, and resignation. In this case, self-acceptance is needed to reduce anxiety and stress experienced by cervical cancer sufferers. Anxious situations will activate the Hypothalamic Pituitary Adrenal axis (HPA axis) and then in the end will triggered the secretion the main of stress hormone, namely glucocorticoids (cortisol). Family function on the process of self-acceptance in cancer patients can be measured using the McMaster Family. This study aims to determine the effect of family function on cervical cancer patient self-acceptance in the McMaster Family method based on a literature review. Libraries in the form of articles and literature books are obtained through the Google search engine, Google Scholar, Elsevier, Cochrane, and PubMed. The study result showed that there was an effect of family function on the self-acceptance of cervical cancer sufferers, the higher the value of family function obtained by the McMaster Family method, the greater the self-acceptance of patients suffering from cervical cancer